2017
DOI: 10.1042/cs20170981
|View full text |Cite
|
Sign up to set email alerts
|

Understanding a role for hypoxia in lesion formation and location in the deep and periventricular white matter in small vessel disease and multiple sclerosis

Abstract: The deep and periventricular white matter is preferentially affected in several neurological disorders, including cerebral small vessel disease (SVD) and multiple sclerosis (MS), suggesting that common pathogenic mechanisms may be involved in this injury. Here we consider the potential pathogenic role of tissue hypoxia in lesion development, arising partly from the vascular anatomy of the affected white matter. Specifically, these regions are supplied by a sparse vasculature fed by long, narrow end arteries/ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 248 publications
(184 reference statements)
3
58
0
1
Order By: Relevance
“…It has been uncertain whether the reduced perfusion is a physiological response to reduced demand, or whether the reduced perfusion may be causing functional and structural damage, but the evidence that the perfusion deficits are associated with reduced cortical oxygenation indicates that the mismatch between perfusion (oxygen delivery) and oxygen demand is, therefore, responsible for causing damage. The perfusion deficits may expose vulnerable niches in the brain to such severe hypoxia that the local oligodendrocytes die, resulting in pattern III demyelination . The evidence for hypoxia in MS is in agreement with earlier results from microarray and immunohistochemical studies .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been uncertain whether the reduced perfusion is a physiological response to reduced demand, or whether the reduced perfusion may be causing functional and structural damage, but the evidence that the perfusion deficits are associated with reduced cortical oxygenation indicates that the mismatch between perfusion (oxygen delivery) and oxygen demand is, therefore, responsible for causing damage. The perfusion deficits may expose vulnerable niches in the brain to such severe hypoxia that the local oligodendrocytes die, resulting in pattern III demyelination . The evidence for hypoxia in MS is in agreement with earlier results from microarray and immunohistochemical studies .…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this is the first study examining perfusion within the spinal cord in rats with EAE, and it has revealed that the expression of neurological deficit is closely related to hypoperfusion of the spinal cord, and that remission from functional deficits is accompanied by improved perfusion. Hypoperfusion is well established in MS with delayed arterial bolus arrival time, increased mean vascular transit time, and long circulation time . It has been uncertain whether the reduced perfusion is a physiological response to reduced demand, or whether the reduced perfusion may be causing functional and structural damage, but the evidence that the perfusion deficits are associated with reduced cortical oxygenation indicates that the mismatch between perfusion (oxygen delivery) and oxygen demand is, therefore, responsible for causing damage.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the transitional zone between cortical grey and white matter, the subcortical white matter may represent a region in the brain that is less vascularized [15][16][17]. Interestingly, our observational findings regarding vascularity in the cortex revealed that there are usually 2-4 neurovascular units (NVU) capillaries per grid examined and in the transitional zone described there was usually only one NVU capillary at the most with a preponderance of no NVU capillaries per grid examined.…”
Section: Discussionmentioning
confidence: 80%
“…At some point—often around age 40–50—the clinical phenotype may transition to a progressive phase, 64–67 during which further mechanisms, over and above focal inflammatory demyelination, contribute to disease evolution. 68 69 These include mitochondrial dysfunction, 68 hypoxia, 70 iron accumulation 68 and fibrogen deposition, 71 and contribute to amplify neurodegeneration, 68 72 particularly in late-stage disease or older patients, where inflammation is less prominent 53 73 and neuronal loss seems to be relatively independent from demyelination. 10 …”
Section: Ageing With Ms: Time To Intervene In Vascular Disease Prevenmentioning
confidence: 99%
“…Although the association between vascular disease and MS is not fully understood, it is possible that vascular risk factors 94 95 or vascular pathology can cause additional damage to the brains of people with MS, over and above that caused by MS alone. 70 96 97 Although this needs further confirmation, information about patients’ vascular status should be incorporated into clinical trials. MS is a heterogeneous disease, and at the individual level the time to reach the secondary progressive phase is variable.…”
Section: Ageing With Ms: Time To Intervene In Vascular Disease Prevenmentioning
confidence: 99%